2001
DOI: 10.1161/01.cir.103.4.520
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Vascular Reactivity in Growth Hormone Deficiency

Abstract: Background-The reason why patients with growth hormone (GH) deficiency (GHD) are at increased risk for premature cardiovascular death is still unclear. Although a variety of vascular risk factors have been identified in GHD, little is known regarding vascular reactivity and its contribution to premature arteriosclerosis. Methods and Results-We assessed vascular function in 7 childhood-onset, GH-deficient nontreated patients (age 22Ϯ3 years, body mass index [BMI] 25Ϯ1 kg/m 2 ) and 10 healthy subjects (age 24Ϯ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 29 publications
(33 reference statements)
4
49
0
5
Order By: Relevance
“…In the present study, GH did not increase plasma nitrate levels, arguing against a major role of increased nitric oxide production for the observed blood pressure effect. Several studies have shown that GH, or IGF-I, may cause vasorelaxation through endothelium-independent mechanisms (Hasdai et al 1998, Capaldo et al 2001. In line with these data, our finding of increased vascular Kir6·1 mRNA levels by GH supports the notion of an endotheliumindependent vasodilatory mechanism activated by GH.…”
Section: Decreased Vascular Tone By Gh -A Role For the Kir6·1/sur2b Csupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, GH did not increase plasma nitrate levels, arguing against a major role of increased nitric oxide production for the observed blood pressure effect. Several studies have shown that GH, or IGF-I, may cause vasorelaxation through endothelium-independent mechanisms (Hasdai et al 1998, Capaldo et al 2001. In line with these data, our finding of increased vascular Kir6·1 mRNA levels by GH supports the notion of an endotheliumindependent vasodilatory mechanism activated by GH.…”
Section: Decreased Vascular Tone By Gh -A Role For the Kir6·1/sur2b Csupporting
confidence: 90%
“…Besides affecting cardiac structure and contractility (Fazio et al 1997, Longobardi et al 2000, Barreto-Filho et al 2002, both experimental and clinical GH deficiency has been associated with increased systemic vascular resistance (Fazio et al 1997, Longobardi et al 2000 and abnormal vascular reactivity (Rossoni et al 1999, Evans et al 2000, Capaldo et al 2001. Accordingly, an increased prevalence of hypertension (Barreto-Filho et al 2002) and atherosclerotic disease (Pfeifer et al 1999) has been reported among patients with GH deficiency, and hypopituitary patients show increased cardiovascular morbidity and mortality (Rosen & Bengtsson 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients demonstrate normal blood pressure, hypotension or hypertension (for review see (2)). They also have endothelial dysfunction (3) and decreased nitric oxide (NO) formation (4). Several studies have shown the clinical benefits of GH therapy on cardiovascular function in these patients, such as unchanged or decreased systolic and diastolic blood pressure (BP), increased cardiac output (CO), increased heart rate (HR) (4,5), increased NO formation (4) and decreased vascular resistance (5).…”
Section: Introductionmentioning
confidence: 99%
“…In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] . Based on these findings, the loss of GH in humans decreases both blood flow and NO levels, whereas GH replacement restores these vascular responses [27,30,31] , indicating that patients with GH deficiency are at increased cardiovascular risk [32] .…”
Section: Introductionmentioning
confidence: 97%